From the North Sea to the Caribbean Sea: 50 years of maritime delimitation in international jurisprudence - Horna Chicchón, Ángel Valjean (2022)
In this article, the author explains the importance of the evolution of the applicable rules to the delimitation of maritime spaces, taking into consideration the general rules and principles of International Law, customary law and the special and relevant circumstances of each case, making this evolution materialize into a body of rules, the article concludes with a reflection on the current status of the mentioned body.